Herning Kunstmuseum. (Herning : Herning Kunstmuseum, 1985)
Dalsgaard, Sven ; Deyrolle, Jean ; Manzoni, Piero ; Fischer, Egon ; Schwalbe, Ole ; Vasarely, Victor ; Andersen, Henning ; Nielsen, Palle ; Heerup, Henry ; Jacobsen, Egill ; Heiberg, Kasper ; etc.
boek